2010
DOI: 10.1080/09540120903311458
|View full text |Cite
|
Sign up to set email alerts
|

Improving universal precautions and client teaching for rural health workers: a peer-group intervention

Abstract: Health workers can contribute to HIV prevention by minimizing HIV transmission in health facilities and increasing Client teaching. We offered a peer-group intervention for Malawian rural health workers to build their universal precautions and teaching skills. A quasi-experimental design using independent sample surveys and observations compared health workers in an intervention and delayed intervention control district at baseline and at 15 and 30 months postintervention. Controlling for demographic factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…QUALITY MGMT: (on-site supervision was provided for 9-months to HCWs, whereby mentorship and extra training were provided)1. FEASIBILITY: Relative risk ratios comparing intervention to control relative risk showed no difference in improvements in screening, diagnosis, and therapy initiationNone15Jere et al [61]Universal precautions AND HIV prevention associated with universal precautions1. EDUCATE: (provided training for HCWs on universal precautions and HIV preventions; trainings were made dynamic in that they incorporated rehearsal of key skills with feedback)2.…”
Section: Resultsmentioning
confidence: 99%
“…QUALITY MGMT: (on-site supervision was provided for 9-months to HCWs, whereby mentorship and extra training were provided)1. FEASIBILITY: Relative risk ratios comparing intervention to control relative risk showed no difference in improvements in screening, diagnosis, and therapy initiationNone15Jere et al [61]Universal precautions AND HIV prevention associated with universal precautions1. EDUCATE: (provided training for HCWs on universal precautions and HIV preventions; trainings were made dynamic in that they incorporated rehearsal of key skills with feedback)2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that training and the use of safety cannulas for IV administration could lower the incidence of NSI 4 . A 30-month training and teaching program leads to an increase of overall knowledge from 55.61% to 63.47% and leads to less NSI incidents 10 .…”
mentioning
confidence: 99%
“…This paper reports the process evaluation of a peer group intervention for human immunodeficiency virus (HIV) prevention which had positive outcomes for three different target groups in Malawi's Central Region [11][12][13][14][15]. Malawi, with a population of 13.9 million, is one of the poorest countries in the world, with 80% of Malawians living in rural communities characterized by subsistence agriculture, low education and high poverty [16].…”
Section: Introductionmentioning
confidence: 99%